Personal identity as condition of moral and legal responsibility - A. B. Didikin (Омский научный вестник: Серия "Общество. История. Современность")
The paper analyzes the evolution of philosophical approaches to understanding the personal identity problem. The personal identity is considered as a key philosophical idea and a source of justification for the possibility of moral and legal responsibility. Arguments that demonstrate the failure of physicalism in explaining the personal identity, as well as the limitations of the psychological approach to the perception of personal identity as continuing psychological changes are presented. The author substantiates the position on the relationship of the narrative approach with the behavioral context of the formation and justification of the identity of a person as a manifestation of the actions and their interpretation in the light of the results achieved